Guiana dolphin home range analysis based on 11 years of photo-identification research in a tropical estuary - De Faria Oshima, Júlia Emi [UNESP]; De Oliveira Santos, Marcos César (Oxford University Press (OUP), 2016)
Home range studies provide significant insights on social organization and interactions, limiting resources and habitat use. Knowledge on home range and habitat use by Guiana dolphins, Sotalia guianensis, is still scarce. The aim of this study was to identify and analyze individual's home ranges of Guiana dolphins in the Cananéia Estuary (25°03'S, 47°55'W), located in southeastern Brazil. Photo-identification efforts were conducted between 2000 and 2010. From a total of 135,918 pictures taken, 34,086 (25%) were useful for individual identification. Twohundred and five individuals were cataloged based on permanent notches along dorsal fin borders. Of the cataloged individuals, 31 had been identified a minimum of 20 times, on distinct dates, prior to this analysis. Home ranges were estimated for these individuals using 4 methods: minimum convex polygon (MCP), adaptive kernel with least-squares cross-validation (AKLSCV), fixed kernel with reference bandwidth (FKHREF), and fixed kernel with least-squares cross-validation (FKLSCV). The sizes of the estimated home ranges varied between 2.2 and 43.8 km2 ( X = 17.5 km2) with MCP, between 0.8 and 82.5 km2 ( X = 15.6 km2) with AKLSCV, between 3.9 and 244 km2 ( X = 72.4 km2) with FKHREF, and from 0.6 to 70.6 km2 ( X = 13.5 km2) with FKLSCV. Significant differences in size and shape of the generated areas were detected when comparing the 4 tested methods. Variation of individual's home range sizes and an extensive overlap among home ranges of different Guiana dolphins in the Cananéia Estuary provide evidence that the region supports important resources for this species. Therefore, preventing habitat loss in this region is essential to guaranteeing the persistence of this population.
Keywords: Cetacea; Delphinidae; Habitat use; Sotalia guianensis; Spatial analysis